Montgomery–Asberg depression rating scale in clinical practice: Psychometric properties on Serbian patients - Vojvodić, Petar; Andonov, Ana; Stevanović, Dejan; Peruničić Mladenović, Ivana; Mihajlović, Goran; Vojvodić, Jovana (Vojnosanitetski pregled, 2020)
Background/Aim. Various rating scales for depression are avalable, but the Montgomery-Asberg Depression Rating Scale (MADRS) is one of the most frequently used scales. The aim of this study was to analyze the measurement properties of the MADRS Serbian version for quantifying depression severity in the clinical setting. Methods. Two studies have been conducted in order to validate the MADRS. The first study included sixty-four adult patients with major depressive disorder (MDD), with test-retest situation, and the second one included 19 participants (also with MDD), who had six test-retest situations.  Psychometric evaluation included descriptive analysis, internal consistency and test-retest reliability, and concurrent validity (correlations with the Hamilton Depression Rating Scale 17 – HAMD-17). Results. The internal consistency for test-retest reliability was 0.93 in total for the MADRS, and for six test-retest situations was 0.95. The MADRS had one factor structure, with explained variance of 66.26% for the first testing, and 61.29% for the retest. There were statistical significant correlations between the MADRS and HAMD-17 (r = 0.96 for test and r = 0.94 for retest). Also, it was shown a great correlation between all items on the MADRS, and for the instrument in total (r = 0.89). Conclusion. The MADRS was shown good statistical results, and it could be used in everyday clinical practice for discriminating MDD.
Keywords: depression; sensitivity and specificity; severity of illness index; surveys and questionnaires